2010
DOI: 10.5194/acp-10-11115-2010
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements of trace gas emissions from biomass burning of fuel types from the southeastern and southwestern United States

Abstract: Abstract. Vegetation commonly managed by prescribed burning was collected from five southeastern and southwestern US military bases and burned under controlled conditions at the US Forest Service Fire Sciences Laboratory in Missoula, Montana. The smoke emissions were measured with a large suite of state-of-the-art instrumentation including an open-path Fourier transform infrared (OP-FTIR) spectrometer for measurement of gas-phase species. The OP-FTIR detected and quantified 19 gas-phase species in these fires:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
288
6
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(318 citation statements)
references
References 65 publications
23
288
6
1
Order By: Relevance
“…The slope of the regression lines of these individual studies was more gentle than the slope we found for the whole dataset. Lab experiments McMeeking et al, 2009;Burling et al, 2010) also show overall higher correlations between MCE and EF CH 4 than our results for all data for the different vegetation biomes combined.…”
Section: Available Ef Datacontrasting
confidence: 44%
“…The slope of the regression lines of these individual studies was more gentle than the slope we found for the whole dataset. Lab experiments McMeeking et al, 2009;Burling et al, 2010) also show overall higher correlations between MCE and EF CH 4 than our results for all data for the different vegetation biomes combined.…”
Section: Available Ef Datacontrasting
confidence: 44%
“…Emission factors for biomass burning are primarily based on airborne and ground field measurements and measurements from small fires conducted in laboratories. Laboratory studies have shown that emissions of trace gases and particles from biomass burning can vary widely based on the type of fuel burned as well as the phase of combustion (i.e., whether the combustion is in the early "flaming" stages or the later "smoldering" stages) [4]. However, the size, fuel moisture, and combustion characteristics of laboratory fires may not be representative of large-scale wildfires.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized for many years that biomass burning can be a source of elevated NH 3 concentrations (Hegg et al, 1988), and both laboratory (Burling et al, 2010) and field (Akagi et al, 2013(Akagi et al, , 2014 measurements have documented wildfires and prescribed burning as important NH 3 sources in the Southeast. Although Xing et al (2013) estimates that wildfires typically account for only 1-3% of annual NH 3 emissions in the U.S. and 3-10% of annual emissions in SEARCH states, the incidence of wildfires are expected to increase in the Southeast as a result of continuing global change (Liu et al, 2014).…”
Section: Conclusion and Potential Implicationsmentioning
confidence: 99%